Gambaran Kasus Rujukan Persalinan di Klinik Mitra Delima - Nurhaeni, Teni; Ningrum, Widya Maya; Rohita, Tita (Universitas Galuh, 2024)
Labor is a complex and crucial physiological process in a woman's life cycle. It not only marks the end of pregnancy, but also the beginning of a new life. A normal labor process is expected to run smoothly without any complications, both for the mother and baby. This study aims to determine the description of labor referral cases at the Mitra Delima Clinic in Pamarican District in 2024. The research method used is a descriptive approach to know and understand the picture of referral of maternity mothers. The sampling technique used total sampling technique with a sample of 61 respondents. Data analysis using univariate analysis. The results of the study were a small proportion of respondents diagnosed referrals to serotinus respondents as many as 21 respondents (34.4%), a small proportion of respondents diagnosed referrals to early rupture of membranes respondents as many as 16 respondents (26.2%), very few of the respondents diagnosed referrals to prolonged latent phase respondents as many as 14 respondents (23%) and very few of the respondents diagnosed referrals to severe preeclampsia respondents (PEB) as many as 10 respondents (34.4%).The results of the univariate analysis showed that most of the referral respondents were in accordance with the SOP as many as 35 respondents (57.4%) and some of the referral respondents were not in accordance with the SOP as many as 26 respondents (42.6%). And it can be concluded that the description of labor referral cases most of the referral respondents according to the SOP at the Delima Partner Clinic, Pamarican District 2024. Keywords : Case referral, delivery Source.